nd Perception of 2 year MBBS students about online zoom classes during COVID-19 pandemic: A questionnaire-based study - Kumar Singh , Amit; Singh , Anju (Journal of Indian Academy of Forensic Medicine, 2021)
Progress is impossible without change, and those who cannot change their minds cannot change anything” by George Bernard Shaw. Using Zoom technology to deliver lecture, connect students and enable anytime, anyplace learning is increasing in COVID-19 pandemic, however keeping students engaged in online learning is difficult in medical education. The study aimed to determine the student’s perception regarding online classes in Forensic medicine. We used zoom video lectures which can be accessed by students from anywhere. The study was conducted at Mayo Institute of Medical Sciences, Barabanki. It is a cross-sectional questionnaire based study. Analysis was done on percentage wise distribution of various parameters used. The study was conducted among 152 study participants, out of which 82(53.95%) were male and 70(46.06%) were female. Majority of the study participants 95(62.5%) felt online classes help them in understanding the topic adequately. 120(78.9%) respondants perceived that only teacher talks during online classes.140(92.1%) respondents feel major limitation of online class is in regard to practicals. Overall opinion of majority of participants is positive and in favour of online classes to avoid exposure to COVID -19 pandemic. However, practical /clinical exposure will have to be ensured in the training of Indian medical graduates. Normally student’s perception regarding online zoom classes in forensic medicine was determined to be positive. Practical class learning is indispensible in medical education, which will have to be incorporated as situation permit.